Meningkatkan Minat Dan Hasil Belajar Dalam Menelaah Struktur Dan Kaidah Kebahasaan Teks Eksplanasi Melalui Model Pembelajaran Course Review Horay Pada Siswa Kelas Viii-3 Smp Negeri 7 Langsa - Ulfa, Listia (Jurnal Pendidikan Penggerak, 2023)
The purpose of this study was to determine the effectiveness of the CRH learning model on students' interest in studying the structure and rules of language and to find out the increase in student learning outcomes in examining the structure and language rules of explanatory texts. The benefits of this research are as a guide for researchers to increase students' interest and learning outcomes in examining the structure and language rules of explanatory texts. The subjects of this study were 25 students of SMP Negeri 7 Langsa, consisting of 12 boys and 13 girls. The data obtained in this research is descriptive qualitative. The research procedure was carried out in two cycles. The results showed that when the learning process took place, student-centered learning was created. This can be seen from the percentage of student learning completeness in cycle I was 42%, cycle II became 87.5%. The percentage of student activity in the first cycle was 73.61% in the sufficient category, in the second cycle it became 83.33% in the good category. The teacher's ability to carry out the learning process